A teoria da imprevisão nos contratos futuros do agronegócio brasileiro - Octaviani, Tiago (2023)
The present work analyzes the possibility (or not) of applying the theory of unpredictability in future contracts in Brazilian agribusiness, through bibliographical research and jurisprudential analysis, according to the deductive method. Initially, this study addresses the current outstanding role of agribusiness in Brazil, especially in the economic and social sphere, justifying the importance of deepening reflections on the subject and, especially, of greater legal protection for the aforementioned Brazilian sector. Further, the present work discusses the legal regime of contracts in general (including concept, postulates, principles and classification), with special emphasis on future and random contracts, especially those signed within the scope of Brazilian agribusiness. Finally, this study analyzes the possibility (or not) of applying the theory of unpredictability in futures contracts signed in the Brazilian agribusiness sector, since the premise of the binding force of contracts in general can run into new random, insurmountable elements, abnormal and unforeseen events, throughout the development of the agricultural activity, leading the rural producer to the involuntary default of the future agreement, also analyzing the hypotheses, requirements, appropriate ways and examples, in addition to the current jurisprudential analysis on the present matter.